Study of the technical parameters dynamics influence on operational performance of hydraulic single-bucket excavators - R. F. Salikhov; V. B. Permiakov (Вестник СибАДИ, 2024)
Introduction. The development of automobile and road construction is a priority in the Russian economy. Timely putting construction projects in commission increases the requirements for planning of execution mechanized works. The operation of transport and technological machines in construction processes for a long time leads to a decrease in their potential capabilities, including operational productivity. The purpose of the proposed article is to improve the method of calculating the performance of a single-bucket hydraulic excavator (EO), taking into account the operating time.Methods and materials. The performance calculation method takes into account the dynamics of the working pressure in the hydraulic system of the working equipment (GRO), the speed of rotation of the crankshaft (PMVC) from the operating time, regression dependencies were used to describe them. The parameters of the law of distribution of the random value of the working pressure in the hydraulic drive and the rate of its fall for the ‘development and recruitment of soil’ operation were also obtained.Results. Processing of the results of production experiments enables to establish the dependence of changes in the working pressure in the hydraulic system during development and gathering soil, as well as for all technological operations of the working cycle, the rotational frequency of the crankshaft of a single-bucket excavator engine on the operating time. The influence of the working pressure in the hydraulic drive, the rotational speed of the crankshaft of the excavator engine on the supply and hydraulic power, the duration of technological operations is studied. The calculation of the operational productivity of a single-bucket excavator is carried out taking into account the dynamics of parameters reflecting its change over operating time.Discussion and conclusions. It has been established that with an increase in operating time, the operating pressure in the hydraulic drive decreases by an average of 12.7-13.0%, and the decrease in the average operating speed of the crankshaft is 4%. The estimated value of the drop in the average hourly operating performance of the EO, taking into account the deterioration of the technical condition, is 55% in the operating time range from 0 to 10,000 operating hours for the Japanese EO ZX 330 model.